2018
DOI: 10.1001/jamapsychiatry.2018.0284
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Among Bullying by Peers, Disordered Eating Behavior, and Symptoms of Depression During Adolescence

Abstract: Bullying by peers was proximally associated with multiple psychopathologic symptoms, whereas symptoms of disordered eating behavior were a key risk factor for future depressive symptoms and bullying by peers. Interventions aimed at reducing problematic eating behavior in adolescents may attenuate the risk of future depressive symptoms and relational problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 81 publications
5
45
0
2
Order By: Relevance
“…For example, individuals with pre‐existing psychiatric or developmental difficulties can be at higher risk of being victimized because they are viewed as “odd” or “different” by peers (Arseneault, Bowes, & Shakoor, ; Reijntjes et al, ). A recent longitudinal study found that disordered eating behavior in adolescence preceded bullying victimization by peers in a non‐clinical population, underscoring the importance of considering bidirectional relationships between bullying/teasing and EDs (Lee & Vaillancourt, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, individuals with pre‐existing psychiatric or developmental difficulties can be at higher risk of being victimized because they are viewed as “odd” or “different” by peers (Arseneault, Bowes, & Shakoor, ; Reijntjes et al, ). A recent longitudinal study found that disordered eating behavior in adolescence preceded bullying victimization by peers in a non‐clinical population, underscoring the importance of considering bidirectional relationships between bullying/teasing and EDs (Lee & Vaillancourt, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent longitudinal study found that disordered eating behavior in adolescence preceded bullying victimization by peers in a nonclinical population, underscoring the importance of considering bidirectional relationships between bullying/teasing and EDs (Lee & Vaillancourt, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As our study did not assess children before Grade 5 (age 10-11), we cannot ignore the possible influence of early childhood BMI, body dissatisfaction, peer victimization, or other forms of abuse (Veldwijk, Proper, Hoeven-Mulder, & Bemelmans, 2012) on the findings. Finally, although cascade modelling is a robust analytic approach, causal inferences are limited in the absence of a randomized controlled trial (Lee & Vaillancourt, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…105–106). Other predictors of disordered eating are as follows: bullying (Copeland et al, ; Lee & Vaillancourt, ), including weight‐related teasing (Hunger & Tomiyama, ); perfectionism (Boone, Soenens, & Luyten, ); anxiety (Hughes, ); depression (Haynos, Watts, Loth, Pearson, & Neumark‐Stzainer, ; Johnson, Cohen, Kotler, Kasen, & Brook, ); poor relationship with a parent (Cerniglia et al, ; Johnson, Cohen, Kasen, et al, ); and low self‐esteem (Haynos et al, ). Self‐reported depression and anxiety are also often co‐morbid with eating issues in adolescence (Hughes, ), although the research evidence has been of low quality due to methodological problems including small sample sizes, mixed or unclear samples, undeclared sampling biases and diverse assessment methods (Godart et al, ).…”
Section: Introductionmentioning
confidence: 99%